Financing of higher education in Uganda - Kajubi, W. Senteza (Higher Education, 1992)
Uganda faces severe financial constraints which have resulted in a serious decline in the quality of higher education and the government faces an urgent need to find new sources of finance for higher education. At present virtually all tuition costs and students' living expenses are financed from public funds, whereas families must bear a substantial part of the costs of primary and secondary education. This “inverted pyramid” is inequitable and results in substantial transfer of income from poor tax payers to rich parents and their children. This article considers arguments for increased cost recovery and the introduction of student loans and also considers obstacles to student loans in Uganda.
Keywords: High Education, Secondary Education, Public Fund, Substantial Part, Financial Constraint